IL1A rs1800587 associates with chronic noncrisis pain in sickle cell disease. (December 2016) - Hu, Xiaoyu; Jhun, Ellie H; Yao, Yingwei; He, Ying; Molokie, Robert E; Wilkie, Diana J; Wang, Zaijie J
Aim: Pain is prevalent in sickle cell disease (SCD) patients who display great heterogeneity in pain severity and frequency. Hypothesizing that inflammatory factors are involved in the pathogenesis of SCD pain, we focused on the IL1A C/T polymorphism rs1800587 that is an SNP located in a cis -transcriptional regulatory region.Methods: We genotyped IL1A rs1800587 and performed association studies with phenotype data obtained by a multidimensional pain assessment tool using the PAINReportIt ® Questionnaire.Results: Each T allele was associated with a 3.9 increase in composite pain index score (p = 0.04) as determined by multiple linear regression.Conclusion: IL1A rs1800587 may influence chronic pain in SCD.